Transcriptome Analysis Reveals Genes Associated With Sexual Dichromatism of Head Feather Color in Mallard - Ma, Shengchao; Liu, Hehe; Wang, Jianmei; Wang, Lei; Xi, Yang; Liu, Yisi; Xu, Qian; Hu, Jiwei; Han, Chunchun; Bai, Lili; Li, Liang; Wang, Jiwen (Frontiers in Genetics, 2021)
Sexual dimorphism of feather color is typical in mallards, in which drakes exhibit green head feathers, while females show dull head feather color. We showed that more melanosomes deposited in the males' head's feather barbules than females and further form a two-dimensional hexagonal lattice, which conferred the green feather coloration of drakes. Additionally, transcriptome analysis revealed that some essential melanin biosynthesis genes were highly expressed in feather follicles during the development of green feathers, contributing to melanin deposition. We further identified 18 candidate differentially expressed genes, which may affect the sharp color differences between the males' head feathers, back feathers, and the females' head feathers. TYR and TYRP1 genes are associated with melanin biosynthesis directly. Their expressions in the males' head feather follicles were significantly higher than those in the back feather follicles and females' head feather follicles. Most clearly, the expression of TYRP1 was 256 and 32 times higher in the head follicles of males than in those of the female head and the male back, respectively. Hence, TYR and TYRP1 are probably the most critical candidate genes in DEGs. They may affect the sexual dimorphism of head feather color by cis-regulation of some transcription factors and the Z-chromosome dosage effect.